A novel algorithm to detect a QPSK signal with the minimum number of samples - Mohammed, Saleh; Hilmi, Sanusi; Abubakar, Adamu; Haruna, Chiroma; Edi, Sutoyo; Mungad, Mu; Tutut, Herawan (Springer, 2015)
In digital communication the QPSK (quadrature phase-shift keying) signal occupies a special position, from satellite systems through to Local Area Networks (LAN). The QPSK signal can be detected or received using analog or digital receivers. The detection capability of digital receivers relies mainly on the number of samples per signal element and signal-to-noise ratio. The number of samples required by a digital receiver is the bottleneck for detection speed. This paper presents a novel algorithm to detect a QPSK signal with the minimum number of samples, or as few as four samples per symbol. The algorithm relies only on the samples’ polarities, which leads to superior immunity to amplitude noise. The algorithm was simulated and tested using ANSI C++. The results showed that the algorithm is capable of detecting a QPSK signal with minimum Bit Error Rate (BER) at signal-to-noise ratio of 7.57 dB and maximum phase distortion of PI/8.